Monitoramento terapêutico e farmacocinética populacional da amicacina administrada em pacientes internados no Hospital Universitário de Santa Maria - Steffens, Nadine Arnold (2022)
Serious infections in a hospital environment, especially in critically ill patients, continue to be a significant problem for the health systems associated with high morbidity and mortality rates. Amikacin is an important ally in treating serious infections and multidrug-resistant microorganisms. Amikacin plasmatic concentrations after administration of a dose vary widely among patients. Due to the variable pharmacokinetic behavior of antimicrobials in the population, there is a growing interest in the use of therapeutic drug monitoring. In this sense, this study aimed to quantify the plasma concentrations of the antimicrobial amikacin through two different methodologies in patients treated at the University Hospital of Santa Maria (HUSM). Additionally, perform a population pharmacokinetic approach to identify covariates and assess their impact on the main pharmacokinetic parameters. Blood samples from the patients were obtained at different times, in the peak and in trought. The quantification of amikacin in plasma was performed by liquid chromatography coupled to mass spectrometry and fluorescence polarized immunoassay. The determination of individual and population pharmacokinetic parameters was obtained using the Monolix® software. In all, 43 patients participated in the study, and 132 blood samples were collected. The mean trought concentrations was 8.55 μg/mL (0.5 – 57.91 μg/mL). At the peak, the mean was 42.87 μg/mL (0.5 – 113.6 μg/mL). The methodologies for quantifying plasma amikacin concentrations were statistically evaluated by non-linear Passing-Bablok regression and the Bland-Altman plot and showed to be comparable, with an average difference of 0.271 μg/mL between their results, allowing the application of both in the hospital routine. One-compartment population pharmacokinetic models were constructed based on data obtained for patients with normal renal function and with declining renal function. The pharmacokinetic parameters obtained were clearance of 3.44 L/h and volume of distribution of 23.41 L and clearance of 1.03 and volume of distribution of 19.6 L, respectively. Among the covariates evaluated, only dialysis was significant for patients with a decline in renal function. The results obtained in this study support the recommendation for therapeutic monitoring of amikacin in clinical routine, especially for special populations such as critically ill patients and those with renal dysfunction. Furthermore, the constructed popPK models can be useful for dose adjustment and evidence-based decision making.